Dinamika Kebijakan Pemerintah Daerah dalam Memberikan Pengakuan dan Perlindungan Masyarakat Hukum Adat di Maluku - Nasaruddin Umar; Rustam Magun Pikahulan; Syafa'at Anugrah Pradana (Law and Human Rights Policy Strategy Agency, Ministry of Law and Human Rights of The Repub, 2023)
The problem of protecting and recognizing the rights of Customary Law Communities in Indonesia, including in Maluku, from the perspective of local government policies, is still being underestimated, even though Article 18 B paragraph (2) of the constitution has given recognition and respect to the unity of Customary Law Communities and their traditional rights, However is it that to get recognition of the status of customary villages in several negeri in the districts of Maluku and disputes over the mata rumah parentah still occur frequently. This study raises issues regarding legal protection and problems regarding the recognition of the rights of Customary Law Communities in districts/cities in Maluku by using statutory, conceptual approaches and case studies of court decisions relating to the rights of Customary Law Communities. Based on the results of the study it was found that the Provincial Government had issued a policy to provide customary law protection in Maluku which became the basis for establishing customary villages in Ambon City and Tual City, however, there are still regencies that have not provided recognition in the form of regional regulations for establishing customary villages, such as in West Seram Regency and Central Maluku Regency due to weak local government commitment and juridical problems.